Pola Komunikasi Publik Puskesmas Andalas dalam Meningkatkan Partisipasi Masyarakat pada Penggunaan Program Jaminan Kesehatan Nasional (JKN) - Farhan Habibi; Lince Magriasti (Lembaga Yasin AlSys, 2026)
Although public communication strategies in social health insurance programs have received attention in various studies, research specifically discussing the communication patterns of first-level health facilities in encouraging community participation in the National Health Insurance Program (JKN) remains limited. This study aims to describe the public communication patterns implemented by Puskesmas Andalas in increasing community participation in the JKN Program and to identify obstacles and solutions in conveying information about the program. This study used a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving health center staff, BPJS Kesehatan representatives, and community members who were users and non-users of JKN. The data were analyzed through data reduction, data display, and conclusion drawing. The results showed that Puskesmas Andalas implemented integrated public communication patterns through primary face-to-face communication, secondary communication through print and digital media, group communication through health education activities, and two-way communication that provides space for the community to ask questions and submit complaints. These communication patterns contributed to an increase in new participant registration, membership reactivation, and utilization of the free BPJS program. However, their implementation still faced internal obstacles, including weak information coordination with BPJS Kesehatan and the absence of dedicated BPJS officers at the health center, as well as external obstacles, including low public understanding of JKN regulations, economic limitations related to family-based contribution obligations, and the digital divide in the use of social media. The conclusion of this study affirms that continuous, multichannel, and trust-based public communication is an important factor in expanding health coverage at the primary care level. The implications of this study include theoretical contributions to the development of public health communication studies and the application of diffusion of innovations theory, as well as practical implications for primary health institutions and policymakers through the strengthening of scheduled health education activities and the appointment of dedicated officers for JKN Communication, Information, and Education (CIE).